Drawing comics lab : characters, panels, storytelling, publishing, and professional practices - Chapman, Robyn (Lab series (Beverly, Mass.), 2012)
"Do you dream of becoming a comic artist? Drawing Comics Lab covers all of the basic steps necessary to produce a comic, from the first doodle to the finished publication. This easy-to-follow book is designed for the beginning or aspiring cartoonist; both children and adults will find the techniques to be engaging and highly accessible. Featured artists include:- James Sturm- Tom Hart- Jessica Abel- Matt Madden- Eddie Campbell- And many othersStart your comic adventures today with Drawing Comics Lab!"--